ANALISIS KRITIS FILSAFAT MUHAMMAD BĀQIR AL-ṢADR TERHADAP SISTEM EKONOMI NEOLIBERAL - Firdausi; Kholid Al Walid (Kanz Philosophia: A Journal for Islamic Philosophy and Mysticism, 2021)
The neoliberal economic system is an economic system that is used to support economic and political activities in almost all countries. However, a series of failures emerged from the neoliberal economic system. The basic problem with this system is the creation of high economic inequality at the country level and social inequality at the community level. This study aims to prove the fragility of the neoliberal economic system by using Muhammad Bāqir al-Ṣadr’s sharp analysis of Materialism Capitalism. This study uses a literature study method using a qualitative descriptive critical analysis approach, which relies on library research and prioritizes philosophical and theoretical preparation, with the main reference sources being books by Muhammad Bāqir al-Ṣadr, especially Falsafatunā and Iqtiṣādunā. According to Bāqir al-Ṣadr, the Islamic economic system based on the doctrine of Islamic economics is the foundation for the formation of laws relating to the welfare and happiness of society in various aspects of life, including the economy. This economic system is also able to be the answer to the problems posed by various economic systems based on Capitalism and Materialism.